Corporate Social Responsibility in Morocco: Are Small and Medium-Sized Enterprises (SMEs) Socialy Responsible? - Hind Ait MHAMED (al-Uqud : Journal of Islamic Economics, 2020)
CSR's dynamism in Moroccan business is very recent. It was started in 2006 with the initiative of the Moroccan Confederation of business associations (CGEM) through the CSR label. Nowadays, more than 70 companies in the majority of large firms had been labelled. In the same year, the Moroccan Kingdom accedes to the Global Compact. At the policy level, the country has presented its achievements regarding the objectives millennia and began the implementation of the objectives of sustainable development. In this dynamism, what about SMEs? Which are the key importance of the Moroccan economy? Therefore, the study aims to explore the existence of a specific CSR in the Moroccan context by focusing on SMEs' social practices. This study uses a qualitative approach based on a case study method that aimed at a scoping study in Moroccan CSR's nature. Our analysis demonstrates that SMEs' social practices would be socially responsible ones' and would reflect an implicit CSR that explained by the motivations of these practices and the relationship of SMEs with its stakeholders